Pengawasan Pelaksanaan Akad Notaris pada Perbankan Syariah oleh Dewan Pengawas Syariah - Sari, Putri Wulan; Santoso, Budi (Universitas Batanghari Jambi, 2024)
The rapid development of Islamic banking institutions must be supported by effective supervision so that operations are more efficient, so the Sharia Supervisory Board was formed by the National Supervisory Board (DSN) to oversee the application of sharia principles in Islamic banking. This research aims to find out the role of the Sharia Supervisory Board in supervising Islamic financial institutions in Indonesia and the Sharia Supervisory Board (DPS) related to supervising the implementation of contracts by Notary. The method used in this research is doctrinal legal research method using secondary data related to Islamic banking. The results of this study indicate that DPS supervision in Islamic banking is not optimal, which has an impact on the supervision of contracts in Islamic banking, as seen from the many problems in Islamic banking in the form of contract violations contrary to sharia principles. The conclusion of this problem is that the Sharia Supervisory Board (DPS) has not optimally carried out its supervision according to its rules to ensure compliance with sharia principles, as supervisors of Islamic banks must oversee every stage of the financing process to ensure the legal protection of their customers.